Indirect-ELISA technique for the detection of the red rot pathogen m sugarcane (Sacchaarum spp hybrid) and resistance screening - VISWANATHAN, R; PADMANABAN, P; MOHANRAJ, D; JOTHI, R (The Indian Journal of Agricultural Sciences, 2013)
Â A study was conductcd during 1995-97 on the possibility of identifying resistance to red rot pathogen Colleiotrichum faicahum Went in sugarcane based on serological technique. Large number of genotypcs are screcned ror red rot resistance in sugarcane every year. To identify the disease resistance at an early stage a new serological techniquc. enzyme linked immunosorbent assay was developed based on antiserum developed against the fungus. Early detection of the pathogen well before the symptom development was possible in this technique. When different tissues in the infectcd sugarcane plant were screened for antigen titre. root eyes and bud in the nodal region and internodal samples from pith and white spot gave higher values showing more pathogen colonisation. When 20 different sugarcane varieties were subjected to ELISA test after pathogen inoculation. it showed a clear variation in disease resistance among them as in field testing. Further this technique was fOund reliable to screen sugarcane genotypes for red rot resistance at un earlier stage.